Direct Instruction as Alternative Solution in Improving Students Reading Comprehension at SMPN 5 Pujut - Arep, Arep (BAHTRA: Pendidikan Bahasa dan Sastra, 2022)
The research aimed to improve students reading comprehension by using direct instruction at second grade students VII.C class of SMPN 5 Pujut in academic year 2021/2022. The research was classroom action research (CAR) with qualitative and quantitative approaches. The research used four steps namely planning, acting, observing dan reflecting. The subject of the research was students at second grade of VII.C class of SMPN 5 Pujut with total number of the subject 22 students. The instrument used of the research was multiple-choice test with total number of the item 25. The data analyzed used qualitative and quantitative approaches. Based on the data analysis was gotten that the average score ofÂ  in the first cycle 74,5 with classical completeness 50% and in the second cycle the average score of the students 87,5 with classical compactness 100%. Therefore, it took conclusion that there was improvement of the students reading comprehension trough direct instruction at second grade of VII.C class of SMPN 5 Pujut